APPROXIMATION OF ASSIGN’S ORDER OF STRUCTURAL DIVISION’S CHIEF OF LOCAL PUBLIC ADMINISTRATION: THEORETICALLY LEGAL ASPECT - Янчук, Артем Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The article is devoted to issue of appointment procedure of business subdivision’s chief of region, Kyiv and Sevastopol mayor’s offices. The legal and regulatory framework of this problematic was analyzed, between the norms of the current legislation of Ukraine were identified irregularities. The practical recommendations of improvement of legislation and practice in the application of its were given. Ukraine’s effort to integrate into European Union requires from a political elite to modernize its public administration system. Today it’s possible with effective and efficient of central authorities government system as state consolidated tool. Central executive bodies, especially ministries are major figures among of them, which provide for national policy formation and implementation in different spheres. As per today, list of current laws and regulations which determine of central government authorities system’s architecture, especially Law of Ukraine «On Civil Service», Law of Ukraine «About central executive bodies» and others should be revised. Because particular provisions of these laws require of consistency in the part of chief’s assign of structural division of oblast, Kyiv and Sevastopol mayor’s offices. Current legislation of Ukraine on this problematic isn’t bring into line and needs of improvement. On the grounds of court holding obtained, it would make sense to include into Law of Ukraine «On Civil Service» new norms and accordance with them to determine of necessary of procedure of chiefs structural divisions’ assign, dismissal and reassignment by the executive bodies of higher level. Procedure development, terms and responsibilities for disregard of appointment procedure of business subdivision’s chief of region, Kyiv and Sevastopol mayor’s offices demand of additional legislative regulation. In view of improvement of mechanism of appointment, dismissal and reassignment chiefs of organs accountable on healthcare issues need provide the regulation of Law of Ukraine «On Civil Service» with the norms of the special laws, and with the object of prevention of two-valued using to come up with proposals: to pull into a selection board of chiefs of region, Kyiv and Sevastopol mayor’s offices of healthcare officers and which will be established by the chief of region public administration. That is why involvement of Ministry of Health of Ukraine into the appointment procedure of business subdivision’s chief of region, Kyiv and Sevastopol mayor’s offices will ensure by the maximally professional personnel, improvement the mechanisms in healthcare sphere and support the principles of openness, objectivity and equity.